Comparison of tone mapping methods during images processing on liquid crystal displays - A. V. Sycev; A. A. Stepanov; A. G. Smirnov; K. .. Blankenbach (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Image enhancement algorithms improve readability on liquid crystal displays under bright ambient light conditions and are the theme of many researchers and developers. The existing problem is the reflection on the surface of the display under bright light source and is relevant in many applications. Several methods of tone mapping (gamma adaptation), which were compared with existing models related to «improving the image under bright ambient light conditions» are developed.